ENDOVASCULAR STENT INSERTION FOR ABDOMINAL AORTIC ANEURYSM A NURSING PERSPECTIVE - Skulski, Carol (Operating Room Nurses Association of Canada Journal, 2004)
The traditional treatment of an Abdominal Aortic Aneurysm (AAA) is an open aortic abdominal repair. The new alternative to the open surgical intervention is endovascular stent insertion (EVSI). An endovascular stent is a minimal access tube like device used to support the vessel to prevent leaking or rupture of the vessel. This intervention is either an elective or an emergency surgery. Emergency surgery is indicated when the aneurysm is either leaking or ruptured.